Spontaneous Tumor Lysis Syndrome Secondary to Small-Cell Neuroendocrine Carcinoma of Unknown Origin: A Rare Case Report and Literature Review - Phyo Thazin Myint; Hifza Waheed Butt; Taha Alrifai; Carlos Marin (Case Reports in Oncological Medicine)
Spontaneous tumor lysis syndrome (STLS), in the absence of prior chemo or radiation therapy, is rare with solid tumors. Here, we present a case of STLS secondary to a small-cell neuroendocrine tumor of unknown origin in a 66-year-old female patient who presented with abdominal discomfort. Computed tomography (CT) abdomen showed a large tumor mass with peritoneal metastasis, and she developed renal failure from STLS, resulting in the need for hemodialysis. Due to the progressive deterioration and the comorbidities, she opted for comfort care. Timely recognition and intervention of STLS is critical. Further studies evaluating STLS in solid tumor patients are recommended.